DIFFERENTIATION OF METHODS AND MEANS OF PROTECTION OF PATIENTS ‘RIGHTS IN UKRAINE - Ямненко, Тетяна Михайлівна; Овчінніков, Руслан Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to explore the main ways and means of protecting their rights. Research methods: philosophical, general scientific and special legal methods, in particular the dialectical method, the method of analysis, the system-functional method, the formal-logical method, the hermeneutic method. Results: the main ways and means of protection of patients’ rights in Ukraine are generalized. Discussion: it is established that ensuring human rights and freedoms, honor and dignity are the main factors in the formation and development of society. Thus, in the context of democratization of Ukrainian society, the issue of ensuring and protecting the rights, freedoms and legitimate interests of citizens becomes especially acute. And one of the basic non-property rights of a person is the right to health. Today, Ukraine is entering a period of creating a new health care system - a system based on the needs of the population, ie aimed at the patient, respect for his rights, the implementation of basic protection provisions. The proclamation by the Constitution of Ukraine of a person, his life, honor and dignity, inviolability and security as the highest social value determines the duty of the state not only to guarantee, but also to actually ensure the inalienable and inviolable rights of citizens to health care. The concept of the patient and his legal status are clarified; the rights of the patient in Ukraine are characterized. The main ways and means of protecting their rights are considered. However, the issue of their actual provision and compliance is one of the most problematic and requires immediate solution through the improvement of existing and introduction of new mechanisms for their protection, able to quickly and effectively address important legal issues of patients caused by ignorance, non-compliance, non-compliance or direct violation. medical care, state-prescribed legal regulations designed to protect the rights of patients.